COVID-19 and e-wallet usage intention: A multigroup analysis between Indonesia and Malaysia - Hendy Mustiko Aji; Izra Berakon; Maizaitulaidawati Md Husin (Cogent Business & Management, 2020)
Physical distancing policy that is encouraged by the World Health Organization (WHO) has inspired consumers to do contactless activities, including payment transaction. Government authorities in a growing number of countries are taking actions to encourage contactless payments as the COVID-19 pandemic escalates. People are worried that novel coronavirus (SARS-Cov2) can be transmitted through physical money. It drives them to shift to e-wallet. Due to a lack of study on this topic, the present study contributes to the literature by examining the effect of perceived risk, government support, and perceived usefulness on customers' intention to use e-wallet during COVID-19 outbreak. To give more fruitful insight, another major contribution of this study is investigating the group difference between Indonesia and Malaysia in the overall model. Questionnaires are distributed to the respondents by using a proportional sampling technique. As a result, 259 total respondents from Indonesia and 207 from Malaysia are collected. Both countries are selected because Indonesia and Malaysia can be considered as the two-worst countries in ASEAN affected by COVID-19. The model is tested using PLS-Structural Equation Modeling (SEM) approach. The results show that the effects of government support on the intention to use e-wallets differ between countries. Besides, perceived usefulness fully mediated government support-intention to use e-wallets relationship, and partially mediated the effect of perceived risk on intention to use e-wallets.
Keywords: 650; Perceived risk; e-wallet; COVID-19; government support; perceived usefulness; multigroup analysis